Narratives of a transformation: The role of space in the advent of neoliberal planning in Bogotá. - Torino, Giulia (International Planning History Society Proceedings, 2016)
This text aims to explore, with a critical perspective intellectually rooted in postcolonial theory, one among the most controversial urban transformations of postmodern Latin America: the one that took place in Bogotá chiefly between 1993 and 2003, and that dealt primarily with the city’s public space. By focusing on the spatial aspects of change (according to Henri Lefebvre’s trialectics of social, physical and mental space) and, within that, on the urban processes and projects that determined a detachment between imaginary and real Bogotá, the article aims to critically query the most prominent and first case of postmodern urban transformation in Colombia, through the analysis of the contestation that such change introduced between official and unofficial urban narratives. From the analysis of the diversity of urban narratives that emerged from a specific case – the alameda El Porvenir, this work locates the urban transformation experienced by Bogotá within those local/global phenomena of rapid urban development that seem to call with growing force for the epistemological reformulation of the symbology and role of space in postmodern cities, as well as for more critically aware theorisations of its codes of production. The analysis of the narratives emerged from the case of the alameda El Porvenir will help to clarify and, hopefully, start relocating the contested “success” of the neoliberal urban agenda that, locally, has been driving urban transformations in Colombia since then. While, regionally, it has contributed to change the way public space is conceived (and planned) in Latin American cities.